The Influence of Price Perceptions and Service Quality on KAI Access Online Ticket Purchasing Decisions with Trust as Mediation - Kesdu, Nanda Karisma Hadi; Susila, Ihwan (Universitas Dharma Andalas, 2024)
The transportation sector plays a crucial role in facilitating human mobility, moving production factors, and transporting goods to markets. Trains, with their large transportation capacity and dedicated lanes, are a preferred mode of transport. As part of its community service mission, PT. Kereta Api Indonesia aims to ensure that all citizens, including individuals and organizations, experience convenience, comfort, and security. To achieve this, a study was conducted to measure the impact of price perceptions and service quality on purchasing decisions, with customer trust as the mediating factor. The research involved 74 respondents using the KAI Access application, and the analysis was done using the Smart PLS3.0 tool. The results of the assessment showed that price perception and service quality both had a positive and significant impact on trust. Similarly, price perception and service quality independently had a positive and significant effect on purchasing decisions. Trust was found to play a significant role in mediating the influence of both price perception and service quality on purchasing decisions.